A Probe of John Dominic Crossan’s 2022 Book Render Unto Caesar, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
I style my short essay here as a probe because it is exploratory in nature. In it, I use certain points from the work of the American Jesuit Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) to explore possible alignments withcertain points in the Irish American biblical scholar John Dominic Crossan’s 2022 book Render Unto Caesar: The Struggle Over Christ and Culture in the New Testament.